The Effect of Workload and Competence on Employee Performance at the Regional Secretariat of Lahat Regency - Fitri Alhuda; Saparudin Saparudin; Melia Andayani (Universitas Dehasen Bengkulu, 2026)
This study aims to determine how workload and competence partially and simultaneously influence employee performance at the Lahat Regency Regional Secretariat. The sample size for this study was 57 respondents. The sampling method used was incidental sampling. This quantitative study employed multiple linear regression analysis, processed using SPSS software, to produce a regression equation . The results of this study indicate a significant effect between workload and employee performance at the Lahat Regency Regional Secretariat, and a significant effect between competence and employee performance at the Lahat Regency Regional Secretariat. The F-test indicates that workload and competence simultaneously influence employee performance at the Lahat Regency Regional Secretariat.